2020
DOI: 10.1371/journal.pone.0230742
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and sexual dimorphism of the crab Xenograpsus testudinatus from the hydrothermal vent field of Kueishan Island, northeastern Taiwan

Abstract: The sulphur-rich and acidic vent waters of a shallow hydrothermal vent field next to Kueishan Island in Taiwan provide a specific and generally toxic environment. Among only a few aquatic organisms able to survive there, the grapsoid crab Xenograpsus testudinatus is the dominant species with a high population density in the vent area. Here we study the gender-specific distribution, morphological traits, and relationship of wet weight vs. carapace width of this crab. A total of 1120 individuals including 831 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Xenograpsus testudinatus is a secondary consumer that consumes zooplankton directly. The crab X. testudinatus is omnivorous and a scavenger, eating a variety of food, including microbes and different organic debris, according to previous studies (Tseng et al, 2020). Fang et al (2023) reported that by intaking and absorbing suspended particles in Kueishantao waters, vent crabs absorb polycyclic aromatic hydrocarbons.…”
Section: Concerns Regarding the Impact Of Mp Particles On The Health Ofmentioning
confidence: 99%
“…Xenograpsus testudinatus is a secondary consumer that consumes zooplankton directly. The crab X. testudinatus is omnivorous and a scavenger, eating a variety of food, including microbes and different organic debris, according to previous studies (Tseng et al, 2020). Fang et al (2023) reported that by intaking and absorbing suspended particles in Kueishantao waters, vent crabs absorb polycyclic aromatic hydrocarbons.…”
Section: Concerns Regarding the Impact Of Mp Particles On The Health Ofmentioning
confidence: 99%
“…Morphological changes are used to determine sexual maturity and study allometric growth changes between the changed part and other parts [5,6] . These differences in phenotypes (such as sexual dimorphism) markedly impact the commercial value of crab species [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The diluted water and high concentration of chlorophyll brought by the river have considerable impacts on the marine biogeochemical cycle in the KC region and southern East China Sea (ECS). A volcanic island, Guishan Island, is in the bay; there are hydrothermal vents near the island [1,2], which discharge hydrothermal fluid containing sulfur particles [3], cause carbonate chemical changes in shallow water areas [4][5][6], and affect the habitat of crabs [7], shrimps [8], and fish [9]. In addition, the flow field in the bay also affect the pathways of eels [10,11].…”
Section: Introductionmentioning
confidence: 99%